The impact of ileal pouch‐anal anastomosis on graft survival following liver transplantation for primary sclerosing cholangitis. Issue 3 (8th June 2018) - Trivedi, P. J.; Reece, J.; Laing, R. W.; Slaney, E.; Cooney, R.; Gunson, B. K.; Kamarajah, S. K.; Pinkney, T.; Thompson, F.; Muiesan, P.; Schlegel, A.; Hirschfield, G. M.; et al.
Summary: Background: Liver transplantation is the only life‐extending intervention for primary sclerosing cholangitis (PSC). Given the co‐existence with colitis, patients may also require colectomy; a factor potentially conferring improved post‐transplant outcomes. Aim: To determine the impact of restorative surgery via ileal pouch‐anal anastomosis (IPAA) vs retaining an end ileostomy on liver‐related outcomes post‐transplantation. Methods: Graft survival was evaluated across a prospectively accrued transplant database, stratified according to colectomy status and type. Results: Between 1990 and 2016, 240 individuals with PSC/colitis underwent transplantation (cumulative 1870 patient‐years until first graft loss or last follow‐up date), of whom 75 also required colectomy. A heightened incidence of graft loss was observed for the IPAA group vs those retaining an end ileostomy (2.8 vs 0.4 per 100 patient‐years, log‐rank P  = 0.005), whereas rates between IPAA vs no colectomy groups were not significantly different (2.8 vs 1.7, P  = 0.1). In addition, the ileostomy group experienced significantly lower graft loss rates vs. patients retaining an intact colon ( P  = 0.044). The risks conferred by IPAA persisted when taking into account timing of colectomy as related to liver transplantation via time‐dependent Cox regression analysis. Hepatic artery thrombosis and biliary strictures were the principal aetiologies of graft loss overall. Incidence rates for both were not significantly different between IPAA and no colectomy groups ( P  = 0.092 and P  = 0.358); however, end ileostomy appeared protective ( P  = 0.007 and 0.031, respectively). Conclusion: In PSC, liver transplantation, colectomy + IPAA is associated with similar incidence rates of hepatic artery thrombosis, recurrent biliary strictures and re‐transplantation compared with no colectomy. Colectomy + end ileostomy confers more favourable graft outcomes. Abstract : Linked Content This article is linked to Weinberg and Reddy paper. To view this article visit https://doi.org/10.1111/apt.14896 .